Gene Therapy in Orthopaedics: Progress and Challenges in Pre-Clinical Development and Translation - Watson-Levings, Rachael S.; Palmer, Glyn D.; Levings, Padraic P.; Dacanay, E. Anthony; Evans, Christopher H.; Ghivizzani, Steven C. (Frontiers in Bioengineering and Biotechnology, 2022)
In orthopaedics, gene-based treatment approaches are being investigated for an array of common -yet medically challenging- pathologic conditions of the skeletal connective tissues and structures (bone, cartilage, ligament, tendon, joints, intervertebral discs etc.). As the skeletal system protects the vital organs and provides weight-bearing structural support, the various tissues are principally composed of dense extracellular matrix (ECM), often with minimal cellularity and vasculature. Due to their functional roles, composition, and distribution throughout the body the skeletal tissues are prone to traumatic injury, and/or structural failure from chronic inflammation and matrix degradation. Due to a mixture of environment and endogenous factors repair processes are often slow and fail to restore the native quality of the ECM and its function. In other cases, large-scale lesions from severe trauma or tumor surgery, exceed the body’s healing and regenerative capacity. Although a wide range of exogenous gene products (proteins and RNAs) have the potential to enhance tissue repair/regeneration and inhibit degenerative disease their clinical use is hindered by the absence of practical methods for safe, effective delivery. Cumulatively, a large body of evidence demonstrates the capacity to transfer coding sequences for biologic agents to cells in the skeletal tissues to achieve prolonged delivery at functional levels to augment local repair or inhibit pathologic processes. With an eye toward clinical translation, we discuss the research progress in the primary injury and disease targets in orthopaedic gene therapy. Technical considerations important to the exploration and pre-clinical development are presented, with an emphasis on vector technologies and delivery strategies whose capacity to generate and sustain functional transgene expression in vivo is well-established.